2021
DOI: 10.51620/0869-2084-2021-66-12-718-721
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of acetylcholinesterase activity in brain tumors

Abstract: It has been established that the non-neuronal cholinergic system is related to the oncogenesis which increases the attractiveness of its components as the promising markers of oncologic diseases. The purpose of this work is to evaluate the clinical significance of the analysis of the activity of acetyl cholinesterase as a new marker of gliomas. The activity of acetyl cholinesterase was assessed by photo colorimetric analysis according to the Hestrin method recalculating the activity of the enzyme in the tumor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…Our study found that AChE decreased significantly as the malignancy increased from grade II tumors. This is our finding, Obukhova et al It has also been shown in a similar study (19).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our study found that AChE decreased significantly as the malignancy increased from grade II tumors. This is our finding, Obukhova et al It has also been shown in a similar study (19).…”
Section: Discussionsupporting
confidence: 91%
“…When the averages of AChE enzyme were examined in terms of the number of days hospitalized in the patient group, a statistically significant difference was found between those who had 8-14 (1.05±0. 19) and 15-21 (0.35±0.19; p<0.05) hospitalization days (Figure 5). When we compared the mean levels of TNF-α, BDNF, Caspase-3, AChE, and BChE enzymes among different tumor pathologies in the patient group, there was no statistically significant difference found (p>0.05) for meningioma, epidermoid cyst, hemangioblastoma, and glial tumors.…”
Section: Resultsmentioning
confidence: 92%
“…In another in vivo study, acetylcholinesterase activity in brain gliomas and whole blood was highly intercorrelated, decreasing sharply in both specimens in the grade I to grade IV tumor groups [ 53 ]. Although this study did not meet review criterion #7 (“tumor studies not included”), the major argument for inclusion was that in patients with the lowest grade glioma (I), the levels of the acetylcholinesterase activity were similar to the reference values in the brain and blood obtained from healthy subjects [ 53 ].…”
Section: Resultsmentioning
confidence: 99%